2018
DOI: 10.1038/s41467-018-03021-5
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial hydrogels with biochemical gradients for screening 3D cellular microenvironments

Abstract: 3D microenvironmental parameters control cell behavior, but can be challenging to investigate over a wide range of conditions. Here, a combinatorial hydrogel platform is developed that uses light-mediated thiol-norbornene chemistry to encapsulate cells within hydrogels with biochemical gradients made by spatially varied light exposure. Specifically, mesenchymal stem cells are photoencapsulated in norbornene-modified hyaluronic acid hydrogels functionalized with gradients (0–5 mM) of peptides that mimic cell-ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
151
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 183 publications
(151 citation statements)
references
References 42 publications
0
151
0
Order By: Relevance
“…We had chosen two different tracks for inducing MSC chondrogenesis, i.e., stimulation of receptor mediated signaling (TGF-β1) and cell-to-cell interactions (N-cadherin). [18,29] Though the HAV sequence alone is enough to induce MSC chondrogenesis, a previous study revealed that an elongated HAV sequence such as CLRAHAVDIN was more effective than the short HAV motif. [27] Out of all the peptide sequences in TGF-β1, the binding site exhibiting the maximum reactivity to the TGF-β1 receptor was selected for this study (CESPLKRQ).…”
Section: Manufacturing β-Cd Ppz and Ad-peptidesmentioning
confidence: 99%
See 1 more Smart Citation
“…We had chosen two different tracks for inducing MSC chondrogenesis, i.e., stimulation of receptor mediated signaling (TGF-β1) and cell-to-cell interactions (N-cadherin). [18,29] Though the HAV sequence alone is enough to induce MSC chondrogenesis, a previous study revealed that an elongated HAV sequence such as CLRAHAVDIN was more effective than the short HAV motif. [27] Out of all the peptide sequences in TGF-β1, the binding site exhibiting the maximum reactivity to the TGF-β1 receptor was selected for this study (CESPLKRQ).…”
Section: Manufacturing β-Cd Ppz and Ad-peptidesmentioning
confidence: 99%
“…Depending on the use of specific differentiation inducible factors, including chemicals, proteins, and peptide, the fate of stem cells and ultimate phenotype may vary (e.g., stem cells may differentiate into osteocytes, chondrocytes, myocytes, adipocytes, etc.). [18] Conversely, from the perspective of fine-tuning hydrogels with bioactive molecules, the modification of hydrogel for the stem cell differentiation leads to unpredictable molecular substitutions [19] or physical mixing of bioactive factors. [17] Although recently reported fine-tuned hydrogels were prepared to regulate stem cell differentiation, it is difficult to use them in vivo system owing to the requirement for use of transdermal UV irradiation, which is carcinogenic.…”
Section: Introductionmentioning
confidence: 99%
“…To confirm the accuracy of the screening platform, they created a discrete hydrogel with a specific concentration of HAV and RGD, and analyzed differentiation of MSCs. As a result, they found that the outcome was consistent with that of the screening prediction 50. Similarly, Aizawa et al fabricated agarose hydrogels containing spatial gradient of vascular endothelial GF 165 (VEGF165) 51.…”
Section: Photolithographymentioning
confidence: 62%
“…By using sliding optical mask or by controlling the intensity and exposure time of light, the total amount of energy transferred to hydrogel precursor could be controlled to form biochemical cue gradient. For example, Vega et al developed norbornene‐modified hyaluronic acid (NorHA) hydrogels with dual peptide gradient to investigate the behavior of MSCs over a wide range of conditions 50. Briefly, NorHA precursors containing dithiol (DTT) crosslinker and 0.5 wt% of Irgacure 2959 (Photoinitiator) were initially polymerized under UV‐light irradiation.…”
Section: Photolithographymentioning
confidence: 99%
“…Norbornene‐modified HA (NorHA) was synthesized as previously described . Briefly, HA‐TBA was coupled with 5‐norbornene‐2‐methylamine (TCI Chemicals) in the presence of BOP in anhydrous DMSO under nitrogen for 2 h at room temperature.…”
Section: Methodsmentioning
confidence: 99%